2012
DOI: 10.1128/iai.05756-11
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Can Utilize Multiple Sources of Hyaluronic Acid for Growth

Abstract: ABSTRACTThe mechanisms by whichStreptococcus pneumoniaeobtains carbohydrates for growth during airway colonization remain to be elucidated. The low concentration of free carbohydrates in the normal human airway suggests that pneumococci must utilize complex glycan structures for growth. The glycosaminoglycan hyaluronic acid is present on the apica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
110
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 47 publications
2
110
0
Order By: Relevance
“…Recent studies have focused on the physiological functions and structures of UGLs and have revealed peculiar mechanisms of UGL catalysis using artificial substrates (15) and that UGL gene disruption leads to reduced upper respiratory tract colonization by Streptococcus pneumoniae (19). Specific inhibitors of UGL are therefore expected to provide anti-bacterial drugs with no side effects.…”
mentioning
confidence: 99%
“…Recent studies have focused on the physiological functions and structures of UGLs and have revealed peculiar mechanisms of UGL catalysis using artificial substrates (15) and that UGL gene disruption leads to reduced upper respiratory tract colonization by Streptococcus pneumoniae (19). Specific inhibitors of UGL are therefore expected to provide anti-bacterial drugs with no side effects.…”
mentioning
confidence: 99%
“…The UGL genetic cluster of S. agalacitae is inducibly transcribed in the presence of hyaluronan (10). Recently, the disruption of the UGL genetic cluster in S. pneumoniae has been demonstrated to reduce the bacterial attachment to host cells and the ability to cause infectious diseases (11). These reports indicate the significance of the UGL genetic cluster in bacterial infections.…”
mentioning
confidence: 83%
“…Streptococci such as S. agalactiae, S. pneumoniae, and S. pyogenes include the UGL genetic cluster responsible for the depolymerization (by lyases (HysA and/or HepC) for hyaluronan and/or heparan sulfate), import (by the phosphotransferase system; PTS), and degradation (by UGL) of glycosaminoglycans in the bacterial genomes (10,11) (Fig. 2A).…”
Section: Metabolism Of Unsaturated Uronic Acids From Glycosaminoglycansmentioning
confidence: 99%
See 1 more Smart Citation
“…S. mutans transports GlcN and GlcNAc primarily via the EII Man permease, a fructose:mannose-type EII that is also the dominant transporter for glucose, mannose, and galactose (2)(3)(4). In fact, the PTS is the primary route for amino sugar uptake for most bacteria, providing cells with internalized GlcN-6-phosphate (GlcN-6-P) or GlcNAc-6-phosphate (GlcNAc-6-P) (5)(6)(7). To catabolize these phosphosugars, bacteria produce a GlcNAc-6-P deacetylase, encoded by nagA, that converts GlcNAc-6-P into GlcN-6-P. GlcN-6-P, generated either from GlcNAc by NagA or by PTS transport of GlcN, is deaminated by a GlcN-6-P deaminase (nagB) and concurrently isomerized to fructose-6-P (F-6-P), which can enter the Embden-Meyerhof-Parnas pathway (5).…”
mentioning
confidence: 99%